2021
DOI: 10.1007/s00261-021-03238-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse factors on nonenhanced abdominal CT for long-term continuous ambulatory peritoneal dialysis: a comparative study between patients who withdraw from and maintain long-term peritoneal dialysis

Abstract: Purpose To investigate the imaging features of patients with long-term continuous ambulatory peritoneal dialysis (CAPD) on nonenhanced abdominal CT and to identify adverse factors for long-term CAPD. Methods A total of 109 patients with less than 5 years of CAPD for peritoneal ultrafiltration failure who switched to hemodialysis (withdrawal group) and 23 patients with more than 10 years of CAPD (long-term group) were retrospectively enrolled. Nonenhanced CT manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Advances in imaging techniques are gradually being applied to the field of PD. Peritoneal morphological changes revealed by imaging are found to be relevant to peritoneal function, and are expected to be an important complement to the evaluation of peritoneal function, as exemplified recently by the study reported by Zhang et al [4]. This commentary summarizes previous applications of peritoneal imaging in the assessment of peritoneal function and provides a prospect on the future of an accurate evaluation of peritoneal function.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Advances in imaging techniques are gradually being applied to the field of PD. Peritoneal morphological changes revealed by imaging are found to be relevant to peritoneal function, and are expected to be an important complement to the evaluation of peritoneal function, as exemplified recently by the study reported by Zhang et al [4]. This commentary summarizes previous applications of peritoneal imaging in the assessment of peritoneal function and provides a prospect on the future of an accurate evaluation of peritoneal function.…”
mentioning
confidence: 71%
“…Zhang et al [4] retrospectively included patients who had been converted to hemodialysis with less than 5 years on continuous ambulatory peritoneal dialysis (CAPD) and patients with CAPD for more than 10 years. They found extensive thickening of the parietal peritoneum, severe calcification of the parietal peritoneum, the mesentery and the free margin of the small intestine wall were adverse factors for long-term PD by analyzing their non-enhanced abdominal CT imaging features.…”
mentioning
confidence: 99%